Associations of diabetes mellitus with orthopaedic infections. Issue 1 (2nd January 2016) - Al-Mayahi, Mohamed; Cian, Anais; Kressmann, Benjamin; de Kalbermatten, Benedicte; Rohner, Peter; Egloff, Michael; Jafaar, Jafaar; Malacarne, Sarah; Miozzari, Hermes H.; Uçkay, Ilker
Abstract : Background: Clinical experience suggests that a high proportion of orthopaedic infections occur in persons with diabetes. Methods: We reviewed several databases of adult patients hospitalized for orthopaedic infections at Geneva University Hospitals from 2004 to 2014 and retrieved 2740 episodes of infection. Results: Overall, diabetes was noted in the medical record for 659 (24%) of these cases. The patients with, compared with those without, diabetes had more than five times more foot infections (274/659 [42%] vs 155/2081 [7%]; p < 0.01) and a significantly higher serum C-reactive protein level at admission (median 96 vs 70 mg/L; p < 0.01). Diabetic patients were older (median 67 vs 52 years; p < 0.01), more often male (471 [71%] vs 1398 [67%]; p = 0.04), and had more frequent polymicrobial infections (219 [37%] vs 353 [19%]; p < 0.01), including more gram-negative non-fermenting rods (90 [15%] vs 168 [9%]; p < 0.01). Excluding foot infections from these analyses did not change the statistically significant differences. Diabetes was present in 17% of all infected orthopaedic patients without foot involvement. In Geneva canton, the overall prevalence of diabetes is estimated at 5.1%, while we have found that the prevalence is 13% in our hospitalized adults. Conclusions: Diabetes is present in 24% of all adult patients hospitalized for surgery for an orthopaedic infection, a prevalence that is several times higher than for the general population and twice as high as that for the population of hospitalized patients. Compared with non-diabetics, patients with diabetes have significantly more infections that are polymicrobial, including gram-negative non-fermenting rods.